Potential of CoSpaces Edu Platform as Interactive Learning Media: Student Perspective - Rizky, Istiana; Nurhamidah, Didah (Jurnal Evaluasi dan Pembelajaran, 2024)
The purpose of this study was to determine the potential use of the CoSpaces Edu platform learning media in Indonesian language learning as an interactive media. The method used is a descriptive qualitative method. The data in the study were questionnaire results regarding the potential difficulties experienced by students or prospective educators in implementing the platform. The source of the research data was 5th-semester students of Language and Literature Education at Syarif Hidayatullah State Islamic University Jakarta. The data collection technique was observation through presentations and questionnaire distribution. The data analysis techniques used were 1) reducing data by selecting appropriate data, 2) presenting data descriptively, and 3) drawing conclusions to find out the study results. The results of this study are that the CoSpaces Edu platform has great potential as an interactive learning media with sufficient training and internet conditions and devices that allow it. The right efforts will produce CoSpaces Edu as an interactive and effective learning tool in the teaching and learning process.